تطوير محتوى منهج الكيمياء في ضوء المستحدثات الكيميائية وفاعليتها في تنمية الثقافة العلمية لطلاب المرحلة الإعدادية بالعراق - البياتي، كريم أحمد محمد إسماعيل Albayati, Karim Ahmed Mohamed Ismail; رمضان، حياة علي محمد; الجندي، أمنية السيد Algendy, Omneya Alsayed; أحمد، قصي شهاب Ahmed, Qusay Shehab (جامعة عين شمس - كلية البنات للآداب والعلوم والتربية, 2018)
هدف البحث الحالي إلى تطوير محتوى منهج الكيمياء في ضوء المستحدثات الكيميائية وفاعليتها في تنمية الثقافة العلمية لطلاب المرحلة الإعدادية بالعراق، واتبع الباحث المنهج الوصفي التحليلي والمنهج التجريبي، وقام الباحث بإعداد قائمة بالمستحدثات الكيميائية لتضمينها في المنهج المطور بهدف تنمية أحد أبعاد الثقافة العلمية (الدافعية للتعلم)، وأظهرت النتائج وجود فرق ذو دلالة إحصائية بين متوسط درجات طلاب المجموعة التجريبية في التطبيق القبلي والتطبيق البعدي لمقياس الدافعية للتعلم لصالح التطبيق البعدي، وحجم تأثير استخدام الوحدة المطورة في ضوء المستحدثات الكيميائية في تنمية الدافعية للتعلم كبير، وذو فعالية مقبولة.
The aim of the present research is to develop the content of the chemistry curriculum in the light of the chemical innovations and their effectiveness in the development of the scientific culture of the students of the preparatory stage in Iraq. The researcher followed the analytical descriptive method and the experimental method. The researcher prepared a list of chemical innovations to include them in the developed curriculum in order to develop a dimension of scientific culture The results showed a statistically significant difference between the average scores of the experimental group in the tribal application and the post-application of the motivation scale for learning in favor of the post-application and the size of the effect of using the developed unit in the light Chemical D that in the development of a great motivation to learn, and has a acceptable effectiveness.
Keywords: المرحلة الإعدادية -- المناهج الدراسية -- منهج الكيمياء -- المستحدثات الكيميائية -- الثقافة العلمية -- دافعية التعلم -- العراق